Kecepatan Release Asam Salisilat dari Crosslinked Pectin Film: Pengaruh Konsentrasi CaCl2 sebagai Crosslinker - Marlyn Vebrian Pattiwael; Meytha Sarasvati; Sperisa Distantia (Seminar Nasional Teknik Kimia Kejuangan, 2016)
This research modified pectin with crosslinking method using CaCl2, so the structure could be applied as Drug Delivery System. Salicylic acid, known as an antibiotic, was added to the crosslinked pectin film. The aim of this research was to evaluate the effects of the CaCl2 concentration as a crosslinker on the release rate of salycilic acid from pectin film in the buffer medium. The research included four steps i.e crosslinking pectin film, loading salycilic acid into the crosslinked pectin film, release test of salycilic acid in the buffer medium with pH=7,4, and data analyzing. Based on the research, the higher crosslinker concentration (0.02 g/ml; 0.05 g/ml; 0.1 g/ml; and 0.15 g/ml), made the pectin structure was denser, thus the amount of salycilic acid loaded in the film was less. The derived mathematic model could describe the mass transfer of salycilic acid. The higher of CaCl2 concentration caused the equilibrium constant (H) increase in the range around 0.235 until 0.7048, while the rate constant of salycilic acid mass transfer (KCA)tended to decrease, in the range 0.016 until 0.11.